Helicobacter pylori infection is associated with fecal biomarkers of environmental enteric dysfunction but not with the nutritional status of children living in Bangladesh. - Shah Mohammad Fahim; Subhasish Das; Md Amran Gazi; Md Ashraful Alam; Md Mehedi Hasan; Md Shabab Hossain; Mustafa Mahfuz; M Masudur Rahman; Rashidul Haque; Shafiqul Alam Sarker; Ramendra Nath Mazumder; Tahmeed Ahmed (Public Library of Science (PLoS), 2020)
Background Because Helicobacter pylori (H. pylori) infection and Environmental Enteric Dysfunction (EED) follow a similar mode of transmission, there can be a complex interplay between H. pylori infection and EED, both of which can influence childhood growth. We sought to investigate the factors associated with H. pylori infection and identify its relationship with the fecal biomarkers of EED including Myeloperoxidase (MPO), Neopterin (NEO), Calprotectin, Reg1B and Alpha-1 antitrypsin (AAT), and nutritional status of the children. Methodology Data from an on-going community-based nutrition intervention study was used for this analysis. Total 319 children aged between 12-18 months were evaluated at enrolment and at the end of a 90-day nutrition intervention. Multivariable linear regression with generalized estimating equations was done to examine the association of H. pylori infection with stool biomarker of EED and nutritional status of the children. Principal findings One-fifth of the participants had H. pylori infection at both the time points, with 13.8% overall persistence. Children living in crowded households had higher odds of being infected by H. pylori (AOR = 2.02; 95% CI = 1.02, 4.10; p-value = 0.045). At enrolment, 60%, 99%, 69% and 85% of the stool samples were elevated compared to the reference values set for MPO, NEO, AAT and Calprotectin in the non-tropical western countries. The proportions reduced to 52%, 99%, 67%, and 77% for the same biomarkers after the nutrition intervention. Infection with H. pylori had significant positive association with fecal AAT concentrations (Coefficient = 0.26; 95% CI = 0.02, 0.49; p-value = 0.03) and inverse relationship with Reg1B concentrations measured in the stool samples (Coefficient = -0.32; 95% CI = -0.59, -0.05; p-value = 0.02). However, H. pylori infection was not associated with the indicators of childhood growth. Conclusions The study findings affirmed that the acquisition and persistence of H. pylori infection in the early years of life may exert an adverse impact on intestinal health, induce gut inflammation and result in increased intestinal permeability.